2020
DOI: 10.3389/fgene.2020.590770
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Analysis of the Prognosis-Associated Alternative Polyadenylation Events in Breast Cancer

Abstract: Alternative polyadenylation (APA) is a post-translational modification that occurs during mRNA maturation in humans. Studies suggested that abnormal APA events are associated with the genesis and progression of malignant tumors. Here, we aimed to comprehensively evaluate the prognostic value of APA events involved in breast cancer (BC). Both APA events and clinical information for BC patients were downloaded from The Cancer Genome Atlas (TCGA) database to identify prognosis-related APA events in BC. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Current research mainly focused on the prognostic role of clinical data or gene level, overlooking the transcriptional level. As one of the important post-transcriptional regulatory mechanisms, APA events have shown a potentially robust predictive value for tumor patients (Venkat et al, 2020;Zhang et al, 2020b). Our study confirmed that APA events are valuable predictors for sarcoma patients, no matter whether in general patients or several subgroups.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Current research mainly focused on the prognostic role of clinical data or gene level, overlooking the transcriptional level. As one of the important post-transcriptional regulatory mechanisms, APA events have shown a potentially robust predictive value for tumor patients (Venkat et al, 2020;Zhang et al, 2020b). Our study confirmed that APA events are valuable predictors for sarcoma patients, no matter whether in general patients or several subgroups.…”
Section: Discussionsupporting
confidence: 80%
“…Genes favoring distal PAS usage (long 3’ UTRs) have PDUI scores near 1, whereas genes favoring proximal PAS usage (short 3’ UTRs) have PDUI scores near 0 ( Venkat et al, 2020 ). To construct as credible a set of APA events as possible, only APA events that met the following criteria were included in this study: ( Von Mehren et al, 2018 ) percentage of samples with PDUI value ≥75%; ( Yang et al, 2019 ) average PDUI value ≥0.05 ( Li et al, 2019 ; Zhang et al, 2020b ). All data were downloaded from the public databases hence it was not required to obtain additional ethical approval for our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to serving as molecular sponge for miRNAs, DSCAM-AS1 can regulate carcinogenesis through modulation of alternative splicing and isoform regulation. Alternative polyadenylation events have been found to be correlated with development and progression of cancers ( Zhang et al, 2020c ). Moreover, 3′UTR shortening as another event associated with DSCAM-AS1 can repress expression of tumor-suppressor genes through disturbing competing endogenous RNA interaction ( Park et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate potential application of APA in diagnosis, prognosis, and treatment of human diseases. APA signatures are now considered superior to many traditional clinical markers (Ji & Tian, 2009; Ogorodnikov et al, 2018; Xia et al, 2014; Y. Zhang et al, 2020). Several studies have indicated therapeutic advantage of APA that is targetable through CRISPR/Cas9 molecular editing system to alter or silence of aberrant PA‐sites (Niu et al, 2016; Xie et al, 2014).…”
Section: Apa In Drug Resistance In Cancer Therapy: a Future Perspectivementioning
confidence: 99%